Unveiling Metaverse Social Trends: Analysing Big Data Regarding Online Sports News With LDA-Based Topic Modelling - Ju Chan Na; Eun Joung Kim; Jung Yoon Kim (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The rise of digitalization has led to a significant increase in the attention given to online sports news. In a similar vein, the Metaverse has gone through various stages of evaluation. At present, it is in a developmental phase where real-world socio-economic and cultural activities are seamlessly integrated into a 3D virtual environment. Understanding the impact and implications of the Metaverse 3.0 era is highly sought after. This study seeks to investigate social issues related to the Metaverse in South Korea. It will analyse a large dataset of online sports news articles from June 2021 to May 2022 using LDA-based topic modelling. As a result, four main topics were identified: a new platform, a new business model, pervasive online cultural and educational media, and a new frontier for business and investment. New Platform (Topic 1) showcased keywords indicating the potential of Metaverse as a cutting-edge platform, while New Business (Topic 2) highlighted keywords indicating digital media companies' pursuit of a new profit model within the virtual realm of Metaverse. The increasing prevalence of online culture and educational media (Topic 3) highlights the growing demand for a wide range of content that caters to the virtual world's cultural and educational experiences. "New Frontier for Business and Investment (Topic 4) highlights the significant involvement of digital media companies in acquiring investments, technologies, and intellectual property (IP) to gain a competitive edge in the global Metaverse market. This study solely examined online sports data, but future research could encompass a wider range of raw data sources, such as interviews with practitioners, user reviews, and research reports. By doing so, a more comprehensive understanding of the potential challenges that the Metaverse may encounter can be obtained.